Linking Contexts, Intersectionality, and Generations: Toward a Multidimensional Theory of Millennials and Social Change. (June 2020) - Council, LaToya D.; Johnson, Chelsea; Santellano, Karina; Yazdiha, Hajar
While millennials are culturally homogenized as a unitary group, scholarly work has examined the complex historical, economic, and social challenges that shape millennials' heterogeneity. This paper draws on three studies to build on this work, showing how millennials experience and enact social change across different spaces: beauty politics and the natural hair movement, black men shaping new masculinities at work and home, and undocumented students navigating institutions of higher education. We show how different groups of millennials bridge and forge new communities, generate hybridized identities that challenge fixed conceptions of identity, and develop new mechanisms for changing the world around them. From findings that highlight the complexity of intra-group and intra-generational experience, we argue for a multidimensional theory of millennials and social change that links contexts, intersectionality, and generational transmission. Such a framework offers a more systematic way to conceptualize variation as it shapes contentious politics and social change.